Resources for Improving Pediatric Readiness and Quality of Care in Rural Communities and Emergency Departments. Issue 3 (March 2022) - Kothari, Shikha Yashwant; Haynes, Sarah C.; Sigal, Ilana; Magana, Julia N.; Ruttan, Timothy; Kuppermann, Nathan; Horeczko, Timothy; Ludwig, Lorah; Karsteadt, Larry; Chapman, Wendy; Pinette, Vickie; Marcin, James P.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: To share the process and products of an 8-year, federally funded grant from the Health Resources and Services Administration Emergency Medical Services for Children program to increase pediatric emergency readiness and quality of care provided in rural communities located within 2 underserved local emergency medical services agencies (LEMSAs) in Northern California. Methods: In 2 multicounty LEMSAs with 24 receiving hospital emergency departments, we conducted focus groups and interviews with patients and parents, first responders, receiving hospital personnel, and other community stakeholders. From this, we (a regional, urban children's hospital) provided a variety of resources for improving the regionalization and quality of pediatric emergency care provided by prehospital providers and healthcare staff at receiving hospitals in these rural LEMSAs. Results: From this project, we provided resources that included regularly scheduled pediatric-specific training and education programs, pediatric-specific quality improvement initiatives, expansion of telemedicine services, and cultural competency training. We also enhanced community engagement and investment in pediatric readiness. Conclusions: The resources we provided from our regional, urban children's hospital to 2 rural LEMSAs facilitated improvements in a regionalized system of care for critically ill and injured children. Our shared resources framework can be adapted by other regional children's hospitals to increase readiness and quality of pediatric emergency care in rural and underserved communities and LEMSAs.